The Effectiveness of the Involvement of 2024 Election Witnesses on Party Vote Acquisition (PKS Medan Case Study) - Sinaga, Mahmudin Hamzah; Situmorang, Tonny P.; Ridho, Hatta (Universitas Medan Area, 2025)
This article or paper aims to analyze the role and function of political party witnesses in overseeing vote acquisition and evaluate the effectiveness of increasing the number of witnesses on the results of the 2024 election. This study uses a qualitative research method with descriptive research using primary data collection techniques and secondary data; primary data in this Thesis is obtained through interviews and observations, while secondary data is obtained through books, journals, and the Internet. The study results show that the involvement of PKS witnesses in the 2024 election in Medan City effectively maintains the party's vote acquisition. PKS witnesses are essential in overseeing the voting and vote-counting process, ensuring that PKS vote results at the polling stations they monitor remain safe. The training, coordination, and use of technology strategies implemented by PKS contribute significantly to the effectiveness of witnesses in the field. However, challenges such as intimidation and logistical limitations need more attention to improve the quality of supervision in the next election.